2020
DOI: 10.3847/1538-4357/ab6b28
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Gas in the NGC 6240 Merging Galaxy System at the Highest Spatial Resolution

Abstract: We present the highest resolution -15 pc (0.03") -ALMA 12 CO(2-1) line emission and 1.3mm continuum maps, tracers of the molecular gas and dust, respectively, in the nearby merging galaxy system NGC 6240, that hosts two supermassive black holes growing simultaneously. These observations provide an excellent spatial match to existing Hubble optical and near-infrared observations of this system. A significant molecular gas mass, ∼9×10 9 M , is located in between the two nuclei, forming a clumpy stream kinematica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 87 publications
2
38
0
Order By: Relevance
“…Recently, Kollatschny et al (2019), using VLT/MUSE data at a resolution of 75 milliarcsec, have reported the discovery of a third nucleus in this galaxy: the Southern component appears to host two distinct nuclei, separated by 198 pc only. The lack of a radio counterpart for the newly detected nucleus suggests that it could be not active; furthermore, no 12 CO(2-1) emission at its position is detected by ALMA (Treister et al, 2020), in stark contrast with the two previously known nuclei.…”
Section: Discovery and Follow-up Observations Of Dual Agnmentioning
confidence: 56%
“…Recently, Kollatschny et al (2019), using VLT/MUSE data at a resolution of 75 milliarcsec, have reported the discovery of a third nucleus in this galaxy: the Southern component appears to host two distinct nuclei, separated by 198 pc only. The lack of a radio counterpart for the newly detected nucleus suggests that it could be not active; furthermore, no 12 CO(2-1) emission at its position is detected by ALMA (Treister et al, 2020), in stark contrast with the two previously known nuclei.…”
Section: Discovery and Follow-up Observations Of Dual Agnmentioning
confidence: 56%
“…Some of these observations are very detailed and reveal very clumpy structures (e.g. Pereira-Santaella et al 2016Cicone et al 2019) and complex morphologies on different scales, often difficult to describe with simple models (Combes et al 2014;Tsai et al 2012;Sakamoto et al 2014;García-Burillo et al 2014Gallimore et al 2016;Aalto et al 2016;Pereira-Santaella et al 2016;Falstad et al 2017;Pereira-Santaella et al 2018;Herrera-Camus et al 2019a;Treister et al 2020). However, the bulk of these observations are often still limited to the detection of high-velocity wings of the CO transitions, and only marginally resolved.…”
Section: Molecular Gas Componentmentioning
confidence: 99%
“…However, this is unlikely; Figure 5(a) shows that the gas motions appear to be dominated by rotation, as we quantify in Section 4.4. A merger, on the other hand, would likely show dispersion-dominant gas dynamics (e.g., Bournaud et al 2011;Díaz-Santos et al 2016Treister et al 2020). ).…”
Section: Symmetric Line Profile Even If There Is a Close [C Ii]mentioning
confidence: 99%